Assessing species-specific differences for nuclear receptor activation for environmental water extracts. (15th October 2020) - Neale, Peta A.; Grimaldi, Marina; Boulahtouf, Abdelhay; Leusch, Frederic D.L.; Balaguer, Patrick
Highlights: Activation of human and zebrafish nuclear receptors by water extracts evaluated. Wastewater effluent up to 14 times more active in the zebrafish pregnane X receptor. Extracts only active in the human peroxisome proliferator-activated receptor gamma. Less than 10 times difference for most human and zebrafish nuclear receptors. Supports current use of human nuclear receptor assays for water quality monitoring. Abstract: In vitro bioassays are increasingly applied to detect endocrine disrupting chemicals (EDCs) in environmental waters. Most studies use human nuclear receptor assays, but this raises questions about their relevance for evaluating ecosystem health. The current study aimed to assess species-specific differences in the activation or inhibition of a range of human and zebrafish nuclear receptors by different water extracts. Wastewater and surface water extracts were run in transactivation assays indicative of the estrogen receptor (ER), androgen receptor (AR), glucocorticoid receptor (GR), progesterone receptor (PR), mineralocorticoid receptor (MR), pregnane X receptor (PXR) and peroxisome proliferator-activated receptor gamma (PPARγ). The transactivation assays were complemented with competitive binding assays for human AR, GR, PR and MR. In most cases, both human and zebrafish nuclear receptor activity were detected in the water extracts. Only some species-specific differences in potency and activity were observed. Water extracts were more active in zebrafish PXR compared to human PXR whereas the opposite was observed for PPARγ. Further, all water extracts inhibited zebrafish PR, while only one extract showed weak anti-progestagenic activity for human PR. Due to these observed differences, zebrafish nuclear receptor assays may be preferable over human nuclear receptor assays to assess the potential risks of EDCs to aquatic organisms. However, recognizing issues with availability of zebrafish nuclear receptor assays and the relatively small differences in responsiveness for many of the human and zebrafish nuclear receptors, including the widely studied ER, the current study supports the continued use of human nuclear receptor assays for water quality monitoring. Graphical abstract: Image, graphical abstract